THE DIFFERENCES IN THE EFFECTS OF PROPOLIS, SODIUM HYPOCHLORITE, AND EDTA AS AN IRRIGANT SOLUTIONS ON THE MICROHARDNESS OF ROOT CANAL DENTIN: IN-VITRO STUDY - Florencia Farrent Br S. Pandia, Ellen; Soraya Tanjung, Dian; Reni Purba, Member (Fakultas Kedokteran Gigi Unjani, 2025)
Sodium hypochlorite (NaOCl) and EDTA are commonly used irrigants due to their antimicrobial properties and ability to dissolve both organic and inorganic components. However, the use of these chemicals at varying concentrations and durations can affect the physical and chemical properties of root canal dentin. Recently, propolis has gained attention as an alternative irrigant because it shows similar potential to conventional irrigants. The aim of this study is to examine whether there are differences in the effects of propolis extract, NaOCl, and EDTA on the microhardness of root canal dentin. This study utilized 24 single-rooted premolar teeth. The crowns were removed, and the roots were longitudinally split into two halves. Samples were randomly divided into six groups (n=8), each immersed in 8% propolis, 20% propolis, 30% propolis, 2.5% NaOCl, 5% NaOCl, and 17% EDTA. The microhardness of root canal dentin was measured using a Vickers Hardness Tester before and after immersion. Data were analyzed using One Way ANOVA. The results showed that 8% propolis had the smallest decrease in microhardness among all treatment groups, with an average difference in initial and final microhardness of 3.68, followed by 20% propolis, 2.5% NaOCl, 5% NaOCl, 30% propolis, and 17% EDTA. The conclusion of this study is that there are significant differences (p<0.05) among the treatment groups regarding the microhardness of root canal dentin. Extracts of 8% and 20% propolis can be used as alternative irrigants. DOI : 10.54052/jhds.v4n3.p255-264